Micromechanical modelling and interfacial strength prediction of multidirectional laminated fibre reinforced polymers - Bolyky, Ákos; Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E. (Cranfield University, 2017)
Delamination initiation and propagation is a common failure mode in laminated composites that must be considered when assessing damage in composite structures. Delamination usually propagates at the interface between laminas. Current approved testing procedures address the inter-laminar strength in fracture modes I and II for interfaces of unidirectional laminas oriented in the same direction. The aim of this study was to investigate the interlaminar fracture initiation strength in multi-layer lamina interfaces by the use of micromechanical numerical analysis. Representative volumetric elements with randomly distributed fibres and the ability of numerically modelling fibre-matrix interfacial debonding were generated with different ply interfacial orientations. Failure initiation and damage sequences were captured and the global stresses where failure initiated were determined for the studied configurations. Insights on the variations in the strength observed due to the different lamina orientations were provided.